Attachment dimensions and forgiveness of others: A meta-analysis. (November 2019) - Hirst, Shannon L.; Hepper, Erica G.; Tenenbaum, Harriet R.
Forgiveness, as a response to interpersonal transgressions, has multiple societal and individual benefits. Individual differences in attachment have been identified as a predictor not only of forgiveness but of state responses frequently associated with forgiveness. The current meta-analysis is the first systematic analysis of the effect of attachment dimensions (i.e., anxiety and avoidance) on forgiveness of others. Analysis of published and unpublished studies ( k = 26) identified significant, small-to-medium effects of attachment anxiety ( r = −.25) and attachment avoidance ( r = −.18) on forgiveness of others. No significant difference was obtained between measures of state and trait forgiveness. The moderating effects of study paradigm, attachment measure, publication type, and sample population were also investigated. The findings of a stable negative effect of insecure attachment dimensions on forgiveness of others provide a base for future research that may focus on reducing attachment anxiety and avoidance to support forgiveness.